The role of VEGF and TGF-β blood levels for fibroid shrinkage, menorrhagia score, and quality of life improvement after uterine artery embolization for uterine fibroids: a study protocol - Aimagambetova, Gulzhanat; Bapayeva, Gauri; Ukybassova, Talshyn; Zemlyanskiy, Viktor; Gusmanov, Arnur; Terzic, Milan (Frontiers in Medicine, 2024)
Uterine leiomyoma are the most common neoplasm affecting women and occur in over 70% of women by the onset of menopause. Women with myomas have compromised overall quality of life and impairment in many specific domains including work productivity, sexuality, self-image, relationships, and social-emotional, and physical well-being that might be present even in pre-and extended throughout early postmenopausal life. Options for symptomatic fibroid treatment include expectant, medical, interventional radiology procedures, and surgical management. The uterine artery embolization (UAE) procedure has gained justified popularity for myoma management. Growth factors such as vascular endothelial growth factor (VEGF) and tumor growth factor β (TGF-β) play an important role in leiomyoma development. However, blood levels of VEGF and TGF-β in patients before and after UAE are not fully investigated and the possible relationship with myoma shrinkage has not been evaluated. Therefore, this study aims to assess menorrhagia score and quality of life improvement after UAE for uterine fibroids and compare blood levels of VEGF and TGF-β in patients with uterine leiomyoma before and after UAE. This cross-sectional study will be performed at the University Medical Center, Astana, Kazakhstan. Women undergoing the UAE procedure for uterine leiomyoma will be involved in the study following the precisely defined inclusion/exclusion criteria. Uterine leiomyoma nodules' structural changes after UAE will be assessed along with the blood levels of growth factors (VEGF and TGF-β), menorrhagia score, and quality of life. An important outcome of this project will be an investigation of the blood levels of growth factors (VEGF and TGF-β) before and after the procedure and their association with leiomyoma shrinkage in correlation with the menorrhagia score and quality of life changes among patients undergoing UAE.